PENGARUH LITERASI MEMBACA DAN MENULIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA UINSU MEDAN DI ERA SOCIETY 5.0 - Lubis, Marasamin; Zein, Hendra Utama; Lubis, Malim Sutan (JURNAL TARBIYAH, 2023)
This research was conducted to see the influence of reading and writing literacy on the mathematical problem solving abilities of UINSU Medan mathematics education students. This study used a quasi-experimental design by taking the smallest sampling unit, namely students from two classes, PMM-1 for the reading literacy class group and PMM-2 for the writing literacy class group. The sampling technique for this study was saturated sampling, with a sample of 35 students per class. Withdrawal of decisions from this study was carried out using the t test. The results of this study are: (1) there is an effect of reading literacy on the mathematical problem solving abilities of UINSU Medan mathematics education students; (2) there is an influence of writing literacy on the mathematical problem solving abilities of UINSU Medan mathematics education students; (3) there are differences in reading and writing literacy towards the mathematical problem solving abilities of UINSU Medan mathematics education students.